Is aromatherapy effective in obstetrics? A systematic review and meta‐analysis - Di Vito, Maura; Cacaci, Margherita; Martini, Cecilia; Barbanti, Lorenzo; Mondello, Francesca; Sanguinetti, Maurizio; Mattarelli, Paola; Bugli, Francesca (Phytotherapy research, 2021)
The aim of this systematic review is to collect clinical trials conducted using essential oils (EOs) in obstetric symptoms by evaluating if and in which context the aromatherapy practice is effective in obstetrics. The research was conducted by using the databases of EMBASE, Medline, Biosis and Toxcenter, PubMed, and Google Scholar search engine, selecting articles from January 2004 to July 2020. This study was performed according to the MOOSE and PRISMA guidelines. Only the randomized clinical trials were considered, and in cases of multiple publications, it was considered the most up to date information. Biases were highlighted. In the presence of homogeneous data, pooling statistics and meta‐analysis were applied. The research led to 71 articles, 17 of which were eligible. Among the trials selected, eight investigated the effectiveness of EOs on anxiety, depression, and stress. Two concerned the treatment of nausea and vomiting, six evaluated the application of EOs on labor for pain treatment, and two showed the effectiveness in the treatment of episiotomy. The heterogeneity of works carried out so far has made it possible to develop a meta‐analysis only in the field of pain treatment during childbirth, identifying the effectiveness of the EOs Lavandula spp. and Rosa damascena.